Organizational communication satisfaction and job satisfaction within university foodservice - Ramirez, Daniel Lopez (Kansas State University, 2012)
Satisfaction with internal communication is important in all organizations and is influenced by the quality and consistency of communication exchange. Job satisfaction is also widely studied in organizations and plays a significant role in employee behavior. Job satisfaction typically correlates with communication satisfaction across different occupations, yet little is known about the communication and job satisfaction relationship in the hospitality industry or specific foodservice organizations. This study explored multiple facets of communication and job satisfaction in a university foodservice setting using the Communication Satisfaction Questionnaire and the Abridged Job Descriptive Index. Results indicated that student employees had the highest levels of communication satisfaction (M=181.75±38.24) while classified employees reported lower communication satisfaction (M=161.00±35.04). Managers reported the lowest levels of communication satisfaction (M=156.17±30.34) and also expressed the highest job satisfaction (M=78.66±18.66). Substantial relationships between job and communication satisfaction were not clearly defined in this study; however, specific themes and opportunities for future research were discovered. Results of this study advance the knowledge about communication and job satisfaction in the foodservice environment.
Keywords: Communication satisfaction; Job satisfaction; University food service; Hospitality; Communication (0459); Higher Education (0745); Higher Education Administration (0446); Labor Relations (0629)